Elevation of Mac‐2 binding protein glycosylation isomer after hepatectomy is associated with post‐hepatectomy liver failure, total Pringle time, and renal dysfunction. Issue 5 (8th July 2019) - Imai, Daisuke; Maeda, Takashi; Wang, Huanlin; Sanefuji, Kensaku; Kayashima, Hiroto; Yoshiya, Shohei; Takeishi, Kazuki; Itoh, Shinji; Harada, Noboru; Ikegami, Toru; Yoshizumi, Tomoharu; Mori, Masaki
Abstract: Background: Mac‐2 binding protein glycosylation isomer (M2BPGi) is a novel serum glycomarker used to assess liver fibrosis. However, it has been reported that M2BPGi is likely to reflect other factors not limited to liver fibrosis. Methods: We retrospectively analyzed 79 patients with liver tumors who underwent liver resection. M2BPGi was measured within 1 week before operation and almost 1 month after operation. We introduced a value termed the "ΔM2BPGi ratio" (=M2BPGiafter operation /M2BPGibefore operation ), and analyzed factors that influenced the ΔM2BPGi ratio. Results: The median value of the ΔM2BPGi ratio was 1.28 (range, 0.36‐5.68). In 64 patients (81.0%), the cutoff index values of M2BPGi were elevated approximately 1 month after operation, especially in patients who experienced post‐hepatectomy liver failure (PHLF). Multiple linear regression showed total Pringle time, PHLF grade ≥B, and preoperative value of creatinine were significant predictors of the ΔM2BPGi ratio. The mean values of the ΔM2BPGi ratio were 1.37 ± 0.07, 1.52 ± 0.22, and 2.94 ± 0.30 for PHLF grade 0, grade A, and grade B, respectively, resulting in statistically significant differences by the Kruskal‐Wallis test ( P = 0.022). Conclusions: Total Pringle time, PHLF grade ≥B, and preoperative creatinine significantly influenced the elevation of M2BPGi almost 1 month after liver resection. This study strongly affirms the previous suggestion that M2BPGi is likely to reflect other factors not limited to liver fibrosis. Abstract : Total Pringle time, PHLF grade ≥B, and preoperative creatinine significantly influenced the elevation of M2BPGi almost 1 month after liver resection. This study strongly affirms the previous suggestion that M2BPGi is likely to reflect other factors not limited to liver fibrosis.